1990
DOI: 10.1063/1.347056
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of HF-treated Si wafer surfaces in air

Abstract: The change in the chemical surface state of polished Si wafers [p-type, (100) oriented] during storage in air at room temperature was investigated for storage times up to half a year. Measurements were performed by x-ray Photoelectron Spectroscopy (XPS) and High Resolution Electron Energy Loss Spectroscopy (HREELS). Immediately after the HF treatment (1 min 5% HF, 2 min water rinse) vibrational spectroscopy (HREELS) shows a predominant coverage of the surface with hydride groups (80%–90% of a ML), which can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(112 citation statements)
references
References 23 publications
8
103
0
1
Order By: Relevance
“…For ambient-air oxidation of bulk-Si surfaces, values ranging from 3 to 170 h have been found, depending on the Si surface index, air humidity, and the initial amount of residual Si-OH groups at the surface. [37][38][39][40][41] According to the Cabrera-Mott mechanism of ambient-air oxidation of bulk-Si and Si-NC surfaces, 20,33,45 the oxidation is initiated by adsorption of water molecules at surface Si-OH groups followed by cleavage of Si-Si backbonds of Si-OH. This is followed by electron transfer from the broken bond to an adsorbed O 2 molecule, which drifts toward the cleaved bond, leading to the oxidation of this bond and of a neighboring Si-Si bond.…”
Section: 29mentioning
confidence: 99%
“…For ambient-air oxidation of bulk-Si surfaces, values ranging from 3 to 170 h have been found, depending on the Si surface index, air humidity, and the initial amount of residual Si-OH groups at the surface. [37][38][39][40][41] According to the Cabrera-Mott mechanism of ambient-air oxidation of bulk-Si and Si-NC surfaces, 20,33,45 the oxidation is initiated by adsorption of water molecules at surface Si-OH groups followed by cleavage of Si-Si backbonds of Si-OH. This is followed by electron transfer from the broken bond to an adsorbed O 2 molecule, which drifts toward the cleaved bond, leading to the oxidation of this bond and of a neighboring Si-Si bond.…”
Section: 29mentioning
confidence: 99%
“…24 Both the phase ∆ AB and the oxide thickness showed slow-fast-slow evolution with time, which has been described previously. [30][31][32][33][34][35] Graf et al investigated the oxidation of H-Si(100) under varying reaction conditions, e.g., immersed in water and in air. 30,31 They found that the oxygen coverage corresponding to the transition region between the slow and the fast growth kinetics is about the same in water (6 × 10 14 O atom/cm 2 ) and in air (4 × 10 14 O atom/cm 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…30,31 They found that the oxygen coverage corresponding to the transition region between the slow and the fast growth kinetics is about the same in water (6 × 10 14 O atom/cm 2 ) and in air (4 × 10 14 O atom/cm 2 ). 30,31 The density of interface atoms at the Si(100) surface is 7 × 10 14 atom/cm 2 . 35 Therefore, it can be assumed that there is a critical coverage (∼0.7 ML) after which the oxide growth is accelerated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wafers were cleaned using HNO 3 to remove organic contaminants and then etched in 1% HF, to remove the native oxide and inorganic particles from the wafer surface. It is known from the literature [6] that silicon surfaces etched in dilute HF solutions are highly resistant to oxidation in air due to the termination with hydrogen. After this the wafers were rinsed just for a few seconds with deionized water using a shower head in order to remove any acid left and then spin dried.…”
Section: Bare Si Wafersmentioning
confidence: 99%